2022
DOI: 10.3390/ijms23126713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psilocybin and Ketamine on Brain Neurotransmitters, Glutamate Receptors, DNA and Rat Behavior

Abstract: Clinical studies provide evidence that ketamine and psilocybin could be used as fast-acting antidepressants, though their mechanisms and toxicity are still not fully understood. To address this issue, we have examined the effect of a single administration of ketamine and psilocybin on the extracellular levels of neurotransmitters in the rat frontal cortex and reticular nucleus of the thalamus using microdialysis. The genotoxic effect and density of glutamate receptor proteins was measured with comet assay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 75 publications
2
58
0
Order By: Relevance
“…A recent study conducted by Wojtas et al indicated that both ketamine and psilocybin increase dopamine, serotonin, glutamate, and GABA extracellular levels in the frontal cortex in rats. These results may support the hypothesis of mTOR signaling and neurogenesis as crucial factors in depression and explain the common antidepressant mechanisms of esketamine and psilocybin [ 50 ].…”
Section: Discussionsupporting
confidence: 84%
“…A recent study conducted by Wojtas et al indicated that both ketamine and psilocybin increase dopamine, serotonin, glutamate, and GABA extracellular levels in the frontal cortex in rats. These results may support the hypothesis of mTOR signaling and neurogenesis as crucial factors in depression and explain the common antidepressant mechanisms of esketamine and psilocybin [ 50 ].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies indicate that spine density is proportional to the excitatory synaptic input to a given neuron (Hering and Sheng, 2001 ). Patients with major depression show low levels of glutamate in prefrontal cortex regions (Arnone et al, 2015 ) and antidepressants increase glutamate concentration in frontal areas (Stone et al, 2012 ; Wojtas et al, 2022 ). Hence, HF-rTMS might exert positive effects on depression-like behavior through the regulation of glutamatergic neurotransmission in mPFC and a consequent increase in spine density and dendritic complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine itself is a drug and a stimulant, and one of its main functions is to increase release of dopamine. Even though many studies reported about the mechanisms of ketamine as antidepressants, ranging from effects on NMDA receptors to effects on GABA receptors [ 22 , 23 ], the major reason for ketamine to exert its antidepressant effect is related to DA release, possibly by activating astrocytic Ca 2+ signaling and changing the bursting of neurons in the Habula nucleus [ 24 ]. Thus, raising brain dopamine is certainly a quick way to change the depressed mood [ 25 ].…”
Section: Monoamine Neurotransmitters Mediate Three Core Effectsmentioning
confidence: 99%